Zapisz w postaci sumy algebraicznej
a)
[tex](x - 4)(x + 1)^{2} [/tex]
b)
[tex](2x - 3)^{2}(x + 2)[/tex]



Odpowiedź :

a) (x-4)(x+1)² = (x-4)(x²+2x+1) = x³ + 2x² + x - 4x² - 8x - 4 = x³ - 2x² - 7x - 4
b) (2x-3)²(x+2) = (4x²-12x+9)(x+2) = 4x³ - 12x² + 9x + 8x² - 24x + 18 = 4x³ - 4x² - 15x + 18

a)

[tex](x-4)(x+1)^2=(x-4)(x^2+2\cdot x\cdot1+1^2)=(x-4)(x^2+2x+1)=\\\\=x^3+2x^2+x-4x^2-8x-4=x^3+2x^2-4x^2+x-8x-4=\boxed{x^3-2x^2-7x-4}[/tex]

b)

[tex](2x-3)^2(x+2)=((2x)^2-2\cdot2x\cdot3+3^2)(x+2)=(4x^2-12x+9)(x+2)=\\\\=4x^3+8x^2-12x^2-24x+9x+18=\boxed{4x^3-4x^2-15x+18}[/tex]

Użyte wzory skróconego mnożenia

  • na kwadrat sumy

[tex](a+b)^2=a^2+2ab+b^2[/tex]

  • na kwadrat różnicy

[tex](a-b)^2=a^2-2ab+b^2[/tex]

Inne Pytanie